2020
DOI: 10.20377/jfr-358
|View full text |Cite
|
Sign up to set email alerts
|

It’s getting late today, please do the laundry: The influence of long-distance commuting on the division of domestic labor

Abstract: The study examines the effect of long-distance commuting on the division of domestic labor in heterosexual couples. A long journey to work can affect other areas of life. Commuters often have lower life satisfaction and their intimate relationships may be impaired by mental stress. When looking at domestic labor the question arises of who is in charge of managing the household and childcare. Do women still adopt the “lion’s share of housework” or take over the “second shift” if they spend part of the day on lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The "Being at the Limit" type includes men who have children but are not particularly involved in childcare. Here, the man's commute could have an impact on the woman's role and responsibility in the household [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "Being at the Limit" type includes men who have children but are not particularly involved in childcare. Here, the man's commute could have an impact on the woman's role and responsibility in the household [39].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that women still bear significantly more responsibility for domestic chores and childcare, which is why they tend to have less time available for work and commuting [37,38]. Consequently, female commuters, especially mothers, tend to commute shorter distances than men but still suffer more from the negative effects on quality of life, well-being and health due to the juggling of family life, work and commuting [36,39,40]. Furthermore, long commutes can have a negative impact on partnerships and parent-child relationships and also influence a person's decision as to when to start a family [41,42].…”
Section: Effects Of Commutingmentioning
confidence: 99%
“…For men working from home, previously invisible housework may have become more noticeable, and they may have become more involved in these tasks if their work areas are shared with other family members and used for other purposes (e.g., as the dining table). Hence, for men in particular, this situation creates new opportunities and demands to increase their contribution to managing the household (e.g., Stenpaß and Kley 2020).…”
Section: Covid-19 Couples’ Division Of Housework and Gender Role Attitudesmentioning
confidence: 99%
“…For men working from home, previously invisible childcare and housework may have become more noticeable, and they may 5 have become more involved in these tasks if their work area is shared with other family members and used for other purposes, e.g., as the dining table, or is located next to the children's play space. Hence, for men in particular, this situation creates new opportunities and demands to increase their contribution to managing the household (e.g., Stenpaß & Kley 2020).…”
Section: Covid-19 Couples' Division Of Housework and Gender Role Attitudesmentioning
confidence: 99%